Exploring the Correlation between Self-regulated Learning Strategies and Academic Success in Higher Education - Smadi, Mona; Al Masri, Amaal A.; Maharmah, Hamza; Abu-snoubar, Tamador (Journal of Ecohumanism, 2024)
This study aims to determine how many Jordanian university students use self-regulated learning strategies, how much these strategies vary by gender and degree of accomplishment, and what the correlation is between students’ strategy possession and their degree of academic success. One hundred twenty male and female students made up the sample. The researcher ensured the validity and reliability of the self-regulated learning techniques questionnaire before administering it to them. The results showed that participants were adequately proficient in listening (mean 3.5, SD 0.8), summarizing (mean 3.7, SD 0.6), and arranging (mean 3.6, SD 0.7), among other tactics. There were clear gender differences; men scored higher on the Listening and Arranging tasks, with the former having a significantly higher mean score (p-value 0.042) and the latter having a slightly higher mean score (3.6). Self-regulated learning strategiesAdditionally, there was a correlation between academic performance and strategy proficiency. High achievers tended to have better scores across the board. However, they were solid in the areas of summarizing (mean 3.9, SD 0.4) and listening (mean 3.8, SD 0.5), where there were strong correlations between the two and academic success (mean 0.59). These findings demonstrate that self-regulated learning strategies are crucial for academic success and that improving these abilities might substantially impact educational performance.